The nonlinear impact of ESG performance on audit pricing: Evidence from China - Yajin Li; Fei Meng (PLoS ONE, 2025)
The substantial impact of corporate Environmental, Social, and Governance (ESG) performance, predominantly measured by non-financial metrics, on external auditors is investigated in this paper. Using a sample of Chinese-listed companies from 2011 to 2021, we examine how auditors respond to corporate ESG performance from the perspective of audit pricing. The findings reveal a U-shaped, non-linear relationship between corporate ESG performance and audit pricing. Enhancing ESG performance significantly reduces audit pricing up to a certain threshold, but the impact diminishes as performance continues to improve. Internal control quality and the degree of information asymmetry play pivotal moderating roles within this U-shaped relationship; higher-quality internal controls and lower information asymmetry contribute to flattening the U-shaped curve. Mechanism analysis illustrates that ESG performance influences audit pricing by mitigating financial and operational risks. This paper supplements the understanding of ESG’s impact on audit pricing from a non-linear perspective, offering valuable insights for companies actively engaged in ESG practices.